Protocol for an implementation study of an evidence-based home cardiac rehabilitation programme for people with heart failure and their caregivers in Scotland (SCOT:REACH-HF). Issue 12 (4th December 2020) - Purcell, Carrie; Daw, Paulina; Kerr, Claire; Cleland, J; Cowie, Aynsley; Dalal, Hasnain M; Ibbotson, Tracy; Murphy, Clare; Taylor, Rod
Abstract : Introduction: Despite evidence that cardiac rehabilitation (CR) is an essential component of care for people with heart failure, uptake is low. A centre-based format is a known barrier, suggesting that home-based programmes might improve accessibility. The aim of SCOT: Rehabilitation EnAblement in CHronic Heart Failure (REACH-HF) is to assess the implementation of the REACH-HF home-based CR intervention in the context of the National Health Service (NHS) in Scotland. This paper presents the design and protocol for this observational implementation study. Specific objectives of SCOT:REACH-HF are to: (1) assess service-level facilitators and barriers to the implementation of REACH-HF; (2) compare real-world patient and caregiver outcomes to those seen in a prior clinical trial; and (3) estimate the economic (health and social) impact of implementing REACH-HF in Scotland. Methods and analysis: The REACH-HF intervention will be delivered in partnership with four 'Beacon sites' across six NHS Scotland Health Boards, covering rural and urban areas. Health professionals from each site will be trained to facilitate delivery of the 12-week programme to 140 people with heart failure and their caregivers. Patient and caregiver outcomes will be assessed at baseline and 4-month follow-up. Assessments include the Minnesota Living with Heart Failure Questionnaire (MLHFQ), five-dimension EuroQol 5L, Hospital Anxiety and Depression Scale, and the Caregiver Burden Questionnaire. Qualitative interviews will be conducted with up to 20 health professionals involved in programme delivery (eg, cardiac nurses, physiotherapists). 65 facilitator-patient consultations will be audio recorded and assessed for fidelity. Integrative analysis will address key research questions on fidelity, context and CR participant-related outcomes. The SCOT:REACH-HF findings will inform the future potential roll-out of REACH-HF in Scotland. Ethics and dissemination: The study has been given ethical approval by the West of Scotland Research Ethics Service (reference 20/WS/0038, approved 25 March 2020). Written informed consent will be obtained from all participants. The study is listed on the ISRCTN registry with study ID ISRCTN53784122 . The research team will ensure that the study is conducted in accordance with both General Data Protection Regulations and the University of Glasgow's Research Governance Framework. Findings will be reported to the funder and shared with Beacon Sites, to facilitate service evaluation, planning and good practice. To broaden interest in, and understanding of REACH-HF, we will seek to publish in peer-reviewed scientific journals and present at stakeholder events, national and international conferences.